Incidence of type 1 diabetes has doubled in Kuwaiti children 0‐14 years over the last 20 years. Issue 8 (16th December 2016) - Shaltout, Azza A.; Wake, Deborah; Thanaraj, Thangavel A.; Omar, Dina M.; Al‐AbdulRazzaq, Dalia; Channanath, Arshad; AlKandari, Hessa; Abdulrasoul, Majedah; Miller, Sophie; Conway, Nicholas; Tuomilehto, Jaakko; Davidsson, Lena; et al.
ABSTRACT: AIMS: This study had 2 aims: to report data on the incidence of childhood‐onset type 1 diabetes in Kuwaiti children aged 0‐14 years during 2011 to 2013 and to compare the recent data with those collected during 1992 to 1997. METHODS: All newly diagnosed patients were registered through the Childhood‐Onset Diabetes eRegistry (CODeR) in 2011‐2013, based on the DiaMond protocol used in 1992‐1997. RESULTS: A total of 515 Kuwaiti children (247 boys and 268 girls) aged 0‐14 years newly diagnosed with type 1 diabetes were registered from 1 January 2011 to 31 December 2013. Data ascertainment were 96.7%. The mean age ± SD at diagnosis was 8.7 ± 3.4 years in boys and 7.9 ± 3.1 years in girls. The crude incidence rate (95% CI) was 40.9 (37.4‐44.6) and the age standardized rate 41.7 (95% 38.1‐45.4) per 100, 000 per year, 39.3 (34.6‐44.4) among boys and 44.1 (39.0‐49.7) among girls. A statistically significant increasing trend in incidence was observed as the overall crude incidence rose from 17.7 in 1992‐1994 to 40.9 per 100, 000 per year in 2011‐2013. The Poisson regression model depicting the trend in incidence revealed that, the incidence rates adjusted for age and sex in 2011 to 2013 was 2.3 (95% CI 1.9‐2.7) times higher than 1992‐1997. CONCLUSIONS: The incidence of type 1 diabetes in Kuwaiti children 0‐14 years has doubled in the last 2 decades. The reasons for this increase requires further investigation.